Photomultiplication‐Type Organic Photodetectors with Fast Response Enabled by the Controlled Charge Trapping Dynamics of Quantum Dot Interlayer. (27th May 2021) - Han, Se Gyo; Lee, Hansol; Choi, Wookjin; Lee, Dongki; Kim, Seunghyun; Sung, Yunmo; Kim, Sungjee; Cho, Kilwon
Abstract: A novel photomultiplication (PM)‐type organic photodiode (OPD) that responds much faster (109 kHz bandwidth) than conventional PM‐type OPDs is demonstrated. This fast response is achieved by introducing quantum dots (QDs) as a PM‐inducing interlayer at the interface between the electrode and the photoactive layer. When the device is illuminated, the photogenerated electrons within the photoactive layer are rapidly transferred and trapped in the trap states of the QD interlayer. The electron trapping subsequently leads to charging of the QD and a consequent shift of the QD energy levels, thereby inducing hole injection from the electrode. This PM mechanism is distinct from that of conventional PM‐type OPDs, whose PM usually requires a long time to induce hole (or electron) injection because of the slow transport and accumulation of electrons (or holes) within the photoactive layer. Because of its PM mechanism, the proposed QD‐interlayer PM‐type OPD achieves high bandwidth and high specific detectivity. In addition, it is demonstrated that the response speed of the proposed device is closely related to the charge trapping/detrapping dynamics of the QDs. This work not only offers a new concept in the design of fast‐responding PM‐type OPDs but also provides comprehensive understanding of the underlying device physics. Abstract : A photomultiplication‐type organic photodiode with dramatically increased response speed is demonstrated. Introduction of a quantum dot interlayer effectively blocks dark current of the device while it rapidly and effectively multiplies photocurrent when illuminated, resulting in high detectivity, external quantum efficiency, and bandwidth of the device. Dependence of device response speed on charge trapping dynamics at the interlayer is also discussed.